Genome-wide analysis of transcription factors related to anthocyanin biosynthesis in carmine radish (Raphanus sativus L.) fleshy roots - Gao, Jian; Peng, Hua; Chen, Fabo; Luo, Mao; Li, Wenbo (PeerJ, 2019)
Carmine radish produced in Chongqing is famous for containing a natural red pigment (red radish pigment). However, the anthocyanin biosynthesis transcriptome and the expression of anthocyanin biosynthesis-related genes in carmine radish have not been fully investigated. Uncovering the mechanism of anthocyanin biosynthesis in the ‘Hongxin 1’ carmine radish cultivar has become a dominant research topic in this field. In this study, a local carmine radish cultivar named ‘Hongxin 1’ containing a highly natural red pigment was used to analyze transcription factors (TFs) related to anthocyanin biosynthesis during the dynamic development of fleshy roots. Based on RNA sequencing data, a total of 1,747 TFs in 64 TF families were identified according to their DNA-binding domains. Of those, approximately 71 differentially expressed transcription factors (DETFs) were commonly detected in any one stage compared with roots in the seedling stage (SS_root). Moreover, 26 transcripts of DETFs targeted by 74 miRNAs belonging to 25 miRNA families were identified, including MYB, WRKY, bHLH, ERF, GRAS, NF-YA, C2H2-Dof, and HD-ZIP. Finally, eight DETF transcripts belonging to the C2C2-Dof, bHLH and ERF families and their eight corresponding miRNAs were selected for qRT-PCR to verify their functions related to anthocyanin biosynthesis during the development of carmine radish fleshy roots. Finally, we propose a putative miRNA-target regulatory model associated with anthocyanin biosynthesis in carmine radish. Our findings suggest that sucrose synthase might act as an important regulator to modulate anthocyanin biosynthesis in carmine radish by inducing several miRNAs (miR165a-5p, miR172b, miR827a, miR166g and miR1432-5p) targeting different ERFs than candidate miRNAs in the traditional WMBW complex in biological processes.
Keywords: Carmine radish; Transcription factors (TFs); microRNAs (miRNAs); Anthocyanin biosynthesis